Significance of using Poloxamer 407 and Lactose in ibuprofen in vitro solubility enhancement - Akhter, Fahima (Brac University, 2020)
This thesis is submitted in partial fulfilment of the requirements for the degree of Bachelor of Pharmacy, 2019.